Physical Activity Recommendations for Adults in Yemen - Hend Al_Madani (Amerta Nutrition, 2020)
Background: Physical inactivity is one of the most crucial global problems in spite of the approved impact of physical activity in enhancing health and preventing NCDs, osteoporosis and many other diseases. Thus, WHO encouraged the countries to set their own physical activity guidelines based on the international physical activity recommendations, however, many countries do not have their national Physical activity recommendations such as Yemen in Eastern Mediterranean Region.Objectives: To suggest proper physical activity recommendations for adults in Yemen based on physical activity recommendations in different countries in WHO regions particularly the Eastern Mediterranean Region.Discussion: Prevalence of national physical activity guidelines and physical activity factors vary among WHO regions. The absence of physical activity recommendations and statistical data in Yemen is obvious and surveillance using validated tools should be done to assess the recent PA and related factors. However, although Yemen has its own issues such as Khat chewing habit and conflict, it shares many factors with other Eastern Mediterranean Region countries in general and Qatar in particular such as unsupportive physical activity environment and limited outdoor activities for women. Conclusion:  Qatar national physical activity guidelines can be suggested as applicable and affordable guidelines for adults in Yemen. According to Qatar guidelines, adults should do (30–60) min of moderate exercise ≥ 5 days per week or (20–60) min of vigorous exercise for ≥3 days per week and in case of promoting or maintaining weight loss, they should do (50-60) minutes daily exercise. Many studies should be done to assess recent physical activity and related barriers to draw evidence-based physical activity guidelines for adults in Yemen.Background: Physical inactivity is one of the most crucial global problems in spite of the approved impact of physical activity in enhancing health and preventing NCDs, osteoporosis and many other diseases. Thus, WHO encouraged the countries to set their own physical activity guidelines based on the international physical activity recommendations, however, many countries do not have their national Physical activity recommendations such as Yemen in Eastern Mediterranean Region.Objectives: To suggest proper physical activity recommendations for adults in Yemen based on physical activity recommendations in different countries in WHO regions particularly the Eastern Mediterranean Region.Discussion: Prevalence of national physical activity guidelines and physical activity factors vary among WHO regions. The absence of physical activity recommendations and statistical data in Yemen is obvious and surveillance using validated tools should be done to assess the recent PA and related factors. However, although Yemen has its own issues such as Khat chewing habit and conflict, it shares many factors with other Eastern Mediterranean Region countries in general and Qatar in particular such as unsupportive physical activity environment and limited outdoor activities for women. Conclusion:  Qatar national physical activity guidelines can be suggested as applicable and affordable guidelines for adults in Yemen. According to Qatar guidelines, adults should do (30–60) min of moderate exercise ≥ 5 days per week or (20–60) min of vigorous exercise for ≥3 days per week and in case of promoting or maintaining weight loss, they should do (50-60) minutes daily exercise. Many studies should be done to assess recent physical activity and related barriers to draw evidence-based physical activity guidelines for adults in Yemen.